Intramolecular Ir(I)-Catalyzed Benzylic C–H Bond Amination of ortho-Substituted Aryl Azides - Sun, Ke (2009)
[Image: see text] Iridium(I) catalyzes the intramolecular benzylic C–H bond amination of ortho-homobenzyl-substituted aryl azides to produce indolines at 25 °C.